Fever induced in rabbits by intraventricular injection of rabbit and human serum albumin. - Morimoto, A (1987)
1. Intraventricular injection of rabbit and human serum albumin, and rabbit endogenous pyrogen produced dose-dependent fevers in rabbits. The pyrogenicity of albumin was less than one-twentieth of the pyrogenicity of endogenous pyrogen. 2. Fevers induced by ventricular albumin were significantly suppressed by intraventricular injection of indomethacin which is a cyclooxygenase inhibitor. In contrast, subcutaneous injection had no effect. 3. Ventricular endogenous pyrogen induced several of the acute phase responses, i.e. decreases in the plasma concentration of iron and zinc, and increases in both the plasma concentration of copper and the white blood cell count. Albumin induced none of these responses. 4. It is concluded that fever induced by ventricular albumin is processed by prostaglandins synthesized within the central nervous system. However, ventricular albumin does not activate the central mechanism to induce acute phase responses.